Diversity within diversity management : country-based perspectives - Georgiadou, Andri; Gonzalez-Perez, Maria Alejandra; Olivas-Lujan, Miguel R. (Advanced series in management ;, 2019)
Nowadays, managing and promoting diversity is of paramount importance to the future of sustainability and the political and business agenda. Despite a tremendous growth in diversity management scholarship in recent years, a strong tendency has emerged whereby existing theories focus on a single level of analysis, using a limited range of mostly Western research settings, and on a narrow range of diversity types. Diversity research has insofar focused on prioritizing visible forms of diversity, such as gender or disability, with less emphasis placed on diversity in culture and values internationally. This edited book provides new practical and strategic insights for practitioners, managers, students and policy makers; it delves into the strategic nature of policy intervention with thought-provoking contributions written by experts from around the world. Contributors aim to provide critical reflection of current debate areas on workplace equality and diversity in under-researched countries to inform and support evidence-based decision making for a wide variety of academic and practice-oriented stakeholders.